THE EFFECT OF NANOEMULSION MOUTHWASH CONTAINING CITRONELLA OIL (Cymbopogon winterianus) AND LEMON OIL (Citrus limon) ON THE NUMBER OF MACROPHAGES IN PREGNANT RAT MODEL INDUCED BY GINGIVITIS - Rahman, Friska Ani; Sunarintyas, Siti; Syaify, Ahmad (Jurnal Medali, 2025)
Background: Pregnancy gingivitis is known to affect high-risk pregnancies. Therefore, preventive treatments are necessary, one of them being use of  mouthwash. Citronella oil and lemon oil have been proven to have anti-inflammatory properties. The aim of this study was to investigate the effectiveness of a nanoemulsion mouthwash combining citronella oil (Cymbopogon winterianus) and lemon oil (Citrus limon),  on macrophage counts in a pregnant rat model induced with gingivitis. Method: Female Sprague Dawley rats were confirmed to be pregnant, followed by ligation of both lower incisor teeth, and then mouthwash application. The rats were routinely fed a moist diet and drinking water containing 10% sucrose. Mouthwash application was performed twice daily (morning and evening) over 7 day. Histological evaluation was conducted by counting the number of macrophages in hematoxylin-eosin preparations. Result: The results showed a reduction in the number of macrophages with the administration of the nanoemulsion mouthwash combining citronella oil and lemon oil. The Mann -Whitney test revealed a significant difference compared to the control group (p<0.05). Conclusion: The nanoemulsion mouthwash with 1% citronella oil and 2,77% lemon oil may help reduce the number of macrophages in pregnant rats with gingivitis.